2018
DOI: 10.1002/2211-5463.12509
|View full text |Cite
|
Sign up to set email alerts
|

The amino‐terminal domain of Mycobacterium tuberculosis ClpB protein plays a crucial role in its substrate disaggregation activity

Abstract: Mycobacterium tuberculosis ( Mtb ) is known to persist in extremely hostile environments within host macrophages. The ability to withstand such proteotoxic stress comes from its highly conserved molecular chaperone machinery. ClpB, a unique member of the AAA + family of chaperones, is responsible for resolving aggregates in Mtb and many other bacterial pathogens. Mtb produces two isoforms of ClpB, a full leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 61 publications
2
9
0
Order By: Relevance
“…Consistent with the autoinhibitory role of the NTD, ΔNClpB is an activated ClpB variant that has tilted MDs and elevated basal ATP hydrolysis rate, and shows high disaggregation activity toward heat-induced aggregates of G6PDH and firefly luciferase. The increased basal ATP activity exhibited by ΔNClpB in comparison to the full-length variant is in good agreement with multiple preceding studies 17 , 19 , 20 , 31 36 and implies that this truncated mutant of ClpB is more wasteful in terms of ATP consumption in the absence of bound substrate–proteins. Our data show unaltered yield and a faster rate of disaggregation following the NTD removal.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with the autoinhibitory role of the NTD, ΔNClpB is an activated ClpB variant that has tilted MDs and elevated basal ATP hydrolysis rate, and shows high disaggregation activity toward heat-induced aggregates of G6PDH and firefly luciferase. The increased basal ATP activity exhibited by ΔNClpB in comparison to the full-length variant is in good agreement with multiple preceding studies 17 , 19 , 20 , 31 36 and implies that this truncated mutant of ClpB is more wasteful in terms of ATP consumption in the absence of bound substrate–proteins. Our data show unaltered yield and a faster rate of disaggregation following the NTD removal.…”
Section: Discussionsupporting
confidence: 91%
“…Based on our results, ΔNClpB is an activated ClpB variant that has tilted MDs, elevated basal ATP hydrolysis rate and high disaggregation activity towards heat-induced aggregates of G6PDH and firefly luciferase. The increased basal ATP activity exhibited by ΔNClpB in comparison to the full-length variant is in good agreement with multiple preceding studies (10,19,20,(28)(29)(30)(31)(32)(33), and implies that this truncated mutant of ClpB is more wasteful in terms of ATP consumption in the absence of bound substrate-proteins. Our data show unaltered yield and faster rate of disaggregation following the NTD removal.…”
Section: Discussionsupporting
confidence: 92%
“…However, accumulating experimental evidence suggests that their role extends beyond substrate-protein binding. Numerous studies reported increased ATP hydrolysis rate by the NTD-truncated mutant ΔNClpB in the absence of protein substrates, compared to the fulllength ClpB, indicating that the NTDs may inhibit futile ATP hydrolysis through yet uncharacterized communication pathways (10,19,20,(28)(29)(30)(31)(32)(33). Indeed, potentially relevant interactions of the NTD with the MD and NBDs in solution were recently detected by X-ray footprinting in Hsp104 (34).…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports illustrate a role of the NTD in regulating ClpB activity. A cryo EM model of ATP-bound E. coli ClpB shows a single NTD that is located on top of the central translocation channel, sealing the pore entrance ( Figure 3 ) ( Deville et al, 2017 ; Tripathi et al, 2018 ). The substrate binding groove of the NTD remains accessible in this state providing a pathway for substrate-induced ClpB activation.…”
Section: Clpb: a Widespread And Partner Controlled Disaggregasementioning
confidence: 99%